2004
DOI: 10.1103/physrevb.70.075309
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence of coupled quantum wells: Effects of indirect excitons in high in-plane magnetic fields

Abstract: Luminescence measurements of a Ga 1−x Al x As/ GaAs double quantum well in in-plane magnetic fields up to 22 T are reported. The properties of spatially direct and indirect excitons are studied. We show that the strong indirect exciton luminescence survives in samples with low nonradiative recombination up to high in-plane magnetic fields. This contrasts with previously published results, where its strong suppression, observed for magnetic fields as low as of 10 T, was explained by the exciton center-of-mass m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…These additional relaxation mechanisms have been reported in experiments [11,12] carried out by our group on DQW systems under conditions equivalent to those mentioned above. A persistent photoluminescence (PL) signal of IXs was observed up to high magnetic fields in these measurements.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…These additional relaxation mechanisms have been reported in experiments [11,12] carried out by our group on DQW systems under conditions equivalent to those mentioned above. A persistent photoluminescence (PL) signal of IXs was observed up to high magnetic fields in these measurements.…”
Section: Introductionmentioning
confidence: 70%
“…Their approach takes account of a real-space electron-hole separation in a biased DQW leading at the finite B k to an exciton state indirect in the reciprocal space. The conservation of the exciton momentum in the direct radiative recombination makes these states optically dark [10], unless some effective way of the momentum relaxation appears.These additional relaxation mechanisms have been reported in experiments [11,12] carried out by our group on DQW systems under conditions equivalent to those mentioned above. A persistent photoluminescence (PL) signal of IXs was observed up to high magnetic fields in these measurements.…”
mentioning
confidence: 70%
“…When the electron and hole carriers are confined in the same region of the direct space and in the same point of the inverse k-space, the exciton is called a direct exciton; alternatively, if the carriers are confined in different regions of the direct space and/or in different points of the inverse k-space the exciton is termed as an indirect exciton. Work on exciton properties have been recently performed both experimentally [1][2][3][4] and theoretically [5][6][7][8][9][10][11][12]. Luminescence measurements in GaAs-Ga 1−x Al x As double quantum wells (QWs) under inplane magnetic fields [1,2] have concluded that the dominating radiative recombination of localized indirect excitons does not allow one to observe the quenching of the spatially indirect exciton luminescence and the quadratic shift of their energy under in-plane magnetic fields, with the consequence that the possibility of an exciton dispersion engineering would then be limited in these kinds of samples.…”
mentioning
confidence: 99%
“…Work on exciton properties have been recently performed both experimentally [1-4] and theoretically [5][6][7][8][9][10][11][12]. Luminescence measurements in GaAs-Ga 1−x Al x As double quantum wells (QWs) under inplane magnetic fields [1,2] have concluded that the dominating radiative recombination of localized indirect excitons does not allow one to observe the quenching of the spatially indirect exciton luminescence and the quadratic shift of their energy under in-plane magnetic fields, with the consequence that the possibility of an exciton dispersion engineering would then be limited in these kinds of samples.Combined theoretical and experimental studies from Ashkinadze et al [11] for the effect of an in-plane magnetic field on the photoluminescence (PL) spectrum of modulation-doped heterostructures have suggested that there are remarkable spectral modifications of the PL spectra in both modulationdoped QWs and high-quality heterojunctions, due to Binduced modifications in the direct optical transitions in QWs, and effects on the free holes in heterojunctions, respectively. Also, studies [12] on the magnetic-field effects on indirect excitons in coupled GaAs-(Ga,Al)As QWs reveal that the exciton effective mass is enhanced as the growth-direction magnetic field increases and, at high fields, it becomes larger than the sum of the e and h masses, suggesting that a magnetoexciton is an excitation with effective mass determined by the coupling [5] between the exciton center of mass (CM) motion and internal structure rather than by the masses of its constituents.…”
mentioning
confidence: 99%
See 1 more Smart Citation